ANATOMICAL PROPERTIES OF FIVE MAJOR WOOD SPECIES CROWN IN JAMBI, SUMATERA - Y I Mandang; Krisdianto Krisdianto (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
General characteristics and anatomical properties of several major wood species in Jambi, Sumatera, have been studied. The purpose is to find out their characters for identification, their appropriate uses and their possibilities to be widely cultivated. Five major wood species have been identified and described: balam (Palaquium gutta Bail.), bayur (Pterospermum diversifolium BI.), medang (Litsea sp.), mahang (Macaranga pruinosa Muell.Arg.) and merkubung (Mac.-ranga gigantea Muell.Arg.). Balam and bayur are suitable for house construction, plywood, furniture: and their fibres are fairly good for pulp. Therefore balam and bayur are highly recommended to be widely cultivated. Mahang and merkubung are too light and soft for construction purposes where strength properties are of prime importance. However mahang and merkubung fibres are of good quality so they still can be recommended to be widely cultivated for pulp source. Medang is fairly appropriate for construction purposes and having fairly good quality fibres as well. However the occurrence of oil cells inside wood tissue and the possible effect of the exudate on gluability and paintability, have to be considered before decision is made for its cultivation in large quantities.